Factors Affecting Low Back Pain (LBP) among Public Transportation Drivers - Muhammad Arma; Indri Seta Septadina; Legiran Legiran (Majalah Kedokteran Sriwijaya, 2019)
Low back pain (LBP) is one of the most common health problems among public transportation drivers. On the average, public transportation drivers has 12 hours working time per day with prolonged static sitting position so that it can cause problems such as muscle and spine pain in the lower back area. This study was conducted to analyze what factors affect LBP the most among public transportation drivers in Palembang. This analytic observational reasearch is using cross sectional design and incidental sampling technique. Subject of the research is 60 public transportation drivers in Palembang. LBP is measured with Nordic Questionnaire and the other factors is measured with self identity questionnaire, Perceived Stress Scale and anthropometric measurement. Data is analysed with Chi-Square method and logistic regression analysis. Thirty seven drivers (61,7%) of 60 drivers complained about LBP. There is significant association of LBP with age (p=0.044), BMI (p=0.006), working period (p=0.037), working time (p=0.040), and smoking (p=0.016), but no significant association with waist circumference (p=0.111), pelvis height (p=0.066), psychosocial stress (p=0.229), and family history(p=0.443). Multivariate analysis with logistic regression showed that BMI is associated with LBP (p=0.002). There is significant association between LBP with age, BMI, working period, working time, and smoking. BMI has a greater association with LBP.